ITO film material for flexible touch screen and preparation method thereof

By introducing a polyvinyl alcohol-silica-methacrylate copolymer layer into the ITO film material, the network structure is formed, and the shortcomings of ITO film material in terms of flexibility, chemical stability, mechanical properties and transparency are solved, and the material performance is more suitable for flexible touch screens and large-size touch screens.

CN119465035BActive Publication Date: 2025-03-25LENGSHUIJIANG JINGKE ELECTRONIC TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510052348.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-03-25
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing ITO film materials have shortcomings in flexibility, chemical stability, mechanical properties and transparency, making them difficult to be suitable for flexible touch screens and large-sized touch screens.

Method used

The structure of a flexible substrate layer, an ITO conductive layer and a polymer layer is adopted. The polymer layer is composed of a polyvinyl alcohol-silica-methacrylate copolymer, which forms a network structure through a specific preparation method to improve the crosslinking degree and mechanical properties of the material.

Benefits of technology

The flexibility, chemical stability, mechanical strength and transparency of the ITO film material is significantly improved, making it more suitable for flexible touch screens and large-sized touch screens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the field of material technology, and in particular to an ITO film material for a flexible touch screen and a preparation method thereof. The ITO film material for a flexible touch screen provided by the present invention comprises a flexible substrate layer, an ITO conductive layer and a polymer layer, wherein the ITO conductive layer is arranged on one surface of the substrate layer, the polymer layer is arranged on a side surface of the ITO conductive layer away from the flexible substrate layer, and the polymer layer component comprises a polyvinyl alcohol-silicon oxide-methacrylate copolymer. The ITO film material provided by the present invention has good flexibility, chemical stability, mechanical strength and transparency, and has good application prospects in the application field of touch screen materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ITO film materials, and in particular to an ITO film material for a flexible touch screen and a preparation method thereof. Background Art

[0002] ITO film materials are widely used in touch screen technology. It has excellent electrical conductivity, high transparency, and strong adhesion to substrate materials such as glass. It is not easy to fall off or be damaged, which ensures the stability and durability of the touch screen. However, it also has some disadvantages that limit its wide application in this field. For example, although ITO material has excellent adhesion and stability, it is relatively brittle and easy to break or crack under external force. With the advent of 5G, flexible consumer electronic products and large touch screen terminals have begun to rise, and ITO is a rigid material. Due to its high resistance and easy breakage, it is difficult to apply to flexible screens and large-size touch screens. In addition, its chemical stability is not excellent enough in certain specific cases.

[0003] In addition to the above problems, the transparency of ITO film materials for touch screens is also an important point of concern in this field. In this field, transparency is often improved by doping oxides, such as doping Nb2O, which has a certain effect, but this method will lead to reduced conductivity. Other methods, such as the transparent electrode structure of a touch screen using an electron beam evaporation method disclosed in Korean patent KR101385951B1, control the extinction coefficient of indium tin oxide (ITO) in the short wavelength band (450nm) in the touch screen panel including the transparent electrode structure, thereby improving the transparency problem, but this method has poor stability and the effect may deteriorate in long-term use. Summary of the invention

[0004] The main purpose of the present invention is to provide an ITO film material for a flexible touch screen and a preparation method thereof, so as to solve the problem that the flexibility, chemical stability, mechanical properties and transparency of the ITO film material in the prior art are not good enough. The specific technical scheme of the present invention is as follows:

[0005] In a first aspect, the present invention provides an ITO film material for a flexible touch screen, comprising a flexible substrate layer, an ITO conductive layer and a polymer layer, wherein the ITO conductive layer is arranged on one surface of the flexible substrate layer, and the polymer layer is arranged on a side surface of the ITO conductive layer away from the flexible substrate layer, and the component of the polymer layer comprises a polyvinyl alcohol-silicon oxide-methacrylate copolymer.

[0006] Preferably, the preparation method of the polyvinyl alcohol-silicon oxide-methacrylate copolymer comprises:

[0007] Step 1, add an appropriate amount of emulsifier and dispersant to deionized water, stir evenly, add PVA, heat until dissolved, and obtain a mixture;

[0008] Step 2, mixing the acrylic acid ester monomer with silica sol, emulsifier and initiator to prepare a pre-emulsion, and slowly dropping it into the mixture obtained in step 1 under heating and stirring conditions. After the dropping is completed, continue to keep the temperature to carry out the polymerization reaction;

[0009] Step 3: After the reaction is completed, the obtained product is separated, washed and dried to obtain a polyvinyl alcohol-silicon oxide-methacrylate copolymer.

[0010] In the above preparation method, the added emulsifier and dispersant help to form a stable emulsion system, ensure that PVA is evenly dispersed in water, and create a good environment for the subsequent polymerization reaction. Subsequently, under the conditions of heating and stirring, the initiator decomposes at an appropriate temperature to produce free radicals, which initiate the polymerization reaction of the monomer. Under the action of the initiator, the acrylate monomer begins to polymerize and may undergo graft copolymerization reaction with the active groups on PVA. At the same time, the silanol groups in the silica sol react and crosslink with the active groups on methacrylate and polyvinyl alcohol.

[0011] Preferably, the mass ratio of the PVA, silica sol and acrylic monomer is 0.25-0.4:0.1:1. Controlling the amount of PVA added within a suitable range is conducive to improving the flexibility of the prepared copolymer; controlling the amount of silica sol added within this range can reduce the impact on the conductivity and stability of the material while increasing cross-linking to improve transparency and strength.

[0012] Preferably, the mass ratio of PVA to deionized water added in step 1 is (0.1-10): (30-100); the amount of water added is controlled to allow the PVA to fully dissolve and facilitate the control of the reaction.

[0013] Preferably, the modulus of the silica sol is 2.8 to 3.2. The silica sol contains active silanol groups, which can undergo cross-linking reactions with hydroxyl groups in polyvinyl alcohol, hydroxyl groups in acrylic monomers with hydroxyl groups, carboxyl groups, etc., and form a certain network structure.

[0014] Preferably, the acrylic acid ester monomer is selected from acrylic acid ester monomers with hydroxyl groups. Acrylic acid ester monomers with hydroxyl groups can increase crosslinking with silica sol and increase the stability of the obtained material.

[0015] More preferably, the hydroxyl-containing acrylic ester monomer is at least one of hydroxyethyl methacrylate, allyl 2-hydroxypropionate and hydroxypropyl methacrylate.

[0016] Preferably, the emulsifiers in step 1 and step 2 include but are not limited to at least one of OP-10 and sodium dodecylbenzene sulfonate; these emulsifiers help to form a stable emulsion system to ensure the smooth progress of the polymerization reaction.

[0017] Preferably, the dispersant in step 1 includes but is not limited to sodium dodecyl sulfate, which is used to improve the stability of the system.

[0018] Preferably, the amount of dispersant and emulsifier added in step 1 is 0.5% to 2% of the mass of PVA.

[0019] Preferably, the amount of the emulsifier added in step 2 is 0.5% to 2% of the mass of the acrylate monomer.

[0020] Preferably, in step 2, the pre-emulsion is added for 20 to 35 minutes. If the pre-emulsion is added for too long, it may cause uneven reaction or produce by-products; and if the pre-emulsion is added for too short a time, it may cause the reaction to be too violent or uncontrollable.

[0021] Preferably, in step 2, the polymerization temperature is 60-80°C, and the reaction time is 2-4 hours. The polymerization temperature is relatively low, which is not conducive to ensuring the effective decomposition of the initiator and the progress of the polymerization reaction; the polymerization temperature and time are controlled within the above range, so that the prepared copolymer has a relatively low molecular weight, which is convenient for controlling the thickness and uniformity of the formed polymer layer. In addition, the relatively low molecular weight is also convenient for obtaining a polymer film with higher flexibility; in addition, high temperature may cause polymer degradation or side reactions, and may also lead to a higher polymer molecular weight, affecting the toughness and transparency of the ITO film material.

[0022] Preferably, in step 2, the initiator includes but is not limited to at least one of ammonium persulfate and potassium persulfate, which plays a role in initiating free radical polymerization in the polymerization reaction, thereby promoting the copolymerization reaction of methyl methacrylate and polyvinyl alcohol.

[0023] Preferably, in step 2, the amount of the initiator added is 0.1% to 1% of the total mass of the PVA and the acrylate monomers.

[0024] Preferably, the thickness of the flexible substrate layer is 10-100 μm, the thickness of the ITO conductive layer is 10-150 nm, and the thickness of the polymer layer is less than 30 μm.

[0025] Preferably, the flexible substrate layer includes one of polyethylene terephthalate (PET), polycarbonate (PC), polyimide (PI), PES (polyester) and PE (polyethylene).

[0026] In a second aspect, the present invention provides a method for preparing an ITO film material for a flexible touch screen, comprising:

[0027] Step 1: depositing an ITO conductive layer on the flexible substrate layer, and then depositing a polyvinyl alcohol-silicon oxide-methacrylate copolymer on the ITO conductive layer to prepare a polymer layer;

[0028] Step 2: Finally, heat treatment is performed at 160-180° C. for 20-60 min to obtain the ITO film material for the flexible touch screen.

[0029] Preferably, the step of depositing a polyvinyl alcohol-silicon oxide-methacrylate copolymer on the ITO conductive layer to prepare the polymer layer comprises the following steps:

[0030] The reactor was kept in an inert atmosphere and heated at room temperature and 10 -6 Polyvinyl alcohol-silicon oxide-methacrylate copolymer is deposited on the surface of the ITO conductive layer at a pressure of torr~1 torr; when depositing in a plasma atmosphere, the RF power is maintained at 20W~1kW.

[0031] Preferably, depositing an ITO conductive layer on the flexible substrate layer comprises the following steps:

[0032] The reactor was maintained in a mixed atmosphere of inert gas and oxygen and heated at room temperature and 10 -6 The target material for forming the ITO conductive layer is deposited on the surface of the flexible substrate layer at a pressure of 0.1 torr to 1 torr.

[0033] Preferably, the inert atmosphere is argon.

[0034] Preferably, the flow rates of the inert gas and oxygen are maintained at 30 sccm to 1000 sccm, respectively.

[0035] The above method is used to prepare the film layer, which is beneficial to improving the bonding strength between interfaces, increasing the service life of the material, and facilitating the control of the thickness of the formed film.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The present invention arranges a polyvinyl alcohol-silicon oxide-methacrylate copolymer polymer layer on the surface of the ITO conductive layer. Since the polymer layer contains silicon oxide, it can provide a certain mechanical strength and improve transparency, and can effectively improve the poor mechanical properties and yellowing problems of the traditional ITO film material such as brittleness; and since the silica sol in the polymer layer is cross-linked with the hydroxyl-bearing acrylic monomer and the polyvinyl alcohol to form a network structure, the copolymer has a higher cross-linking degree, and can provide better strength while providing better flexibility and chemical stability;

[0038] Finally, the ITO film material provided by the present invention has good flexibility, chemical stability, mechanical strength and transparency, and has good application prospects in the field of touch screen materials. DETAILED DESCRIPTION

[0039] In order to enable those skilled in the art to better understand the solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present invention.

[0040] The silica sol used in the examples and comparative examples of the present application was produced by Shandong Yinfeng Nano New Materials Co., Ltd., the polyvinyl alcohol was produced by Shuangxin Environmental Protection Materials Co., Ltd., the methacrylate was produced by Mitsubishi Chemical Corporation; the manufacturer of hydroxyethyl methacrylate, allyl 2-hydroxypropionate and hydroxypropyl methacrylate was Changzhou Haike Chemical Co., Ltd.

[0041] Embodiment 1:

[0042] Preparation of ITO film materials for touch screens:

[0043] Step 1: Preparation of polyvinyl alcohol-silicon oxide-methacrylate copolymer:

[0044] Step 1, add a certain amount of deionized water, and add appropriate amounts of OP-10 and sodium dodecyl sulfate in a reaction container, stir evenly, add PVA, heat to 80°C and stir until completely dissolved to obtain a mixture; wherein the added amounts of OP-10 and sodium dodecyl sulfate are both 1% of the mass of PVA, and the mass ratio of PVA to deionized water is 1:10;

[0045] Step 2, in another container, hydroxyethyl methacrylate is mixed with silica sol (modulus 3.2), OP-10 and ammonium persulfate to prepare a pre-emulsion, and the pre-emulsion is slowly added to the mixture obtained in step 1 under heating to 70°C and stirring conditions, and the dropping time is controlled to be 25 minutes. After the dropping is completed, the temperature is kept for 3 hours to carry out the polymerization reaction; wherein, the OP-10 in the pre-emulsion is 1% of the mass of hydroxyethyl methacrylate, the amount of ammonium persulfate added is 0.5% of the total mass of PVA and hydroxyethyl methacrylate, and the mass ratio of PVA, silica sol and hydroxyethyl methacrylate is 0.3:0.1:1;

[0046] Step 3, after the reaction is completed, the product is separated, washed with ethyl acetate, and dried at 60° C. to obtain a polyvinyl alcohol-silicon oxide-methacrylate copolymer;

[0047] Step 2: The reactor was kept in a mixed atmosphere of argon and oxygen, with the flow rates of argon and oxygen being 300 sccm each, and then heated at room temperature and 10 -3 The ITO conductive layer was deposited on the surface of a 30 μm flexible substrate layer (PET) at a pressure of 10 torr to a thickness of 50 nm; the reactor was then kept in an argon atmosphere of 300 sccm and heated at room temperature and 10 -4 Depositing polyvinyl alcohol-silicon oxide-methacrylate copolymer on the surface of the ITO conductive layer under a pressure of 100 μm until the thickness of the polymer layer reaches 10 μm; during the above deposition process, when depositing in a plasma atmosphere, the RF power is maintained at 800 W;

[0048] Step 3: Then heat treat at 160° C. for 50 min to obtain the ITO film material for the flexible touch screen.

[0049] Embodiment 2:

[0050] Preparation of ITO film materials for touch screens:

[0051] Step 1: Preparation of polyvinyl alcohol-silicon oxide-methacrylate copolymer:

[0052] Step 1, adding a certain amount of deionized water, and adding appropriate amounts of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate to a reaction container, stirring evenly, adding PVA, heating to 80° C. and stirring until completely dissolved, to obtain a mixture; wherein the addition amounts of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate are both 0.5% of the mass of PVA, and the mass ratio of PVA to deionized water is 0.1:30;

[0053] Step 2, in another container, allyl 2-hydroxypropionate is mixed with silica sol (modulus 3.2), sodium dodecylbenzene sulfonate and potassium persulfate to prepare a pre-emulsion, and the pre-emulsion is slowly added dropwise to the mixture obtained in step 1 under heating to 80°C and stirring conditions, and the dropping time is controlled to be 20 minutes. After the dropping is completed, the polymerization reaction is continued by keeping warm for 2 hours; wherein, the amount of sodium dodecylbenzene sulfonate added to the pre-emulsion is 0.5% of the mass of allyl 2-hydroxypropionate, the amount of potassium persulfate added is 0.1% of the total mass of PVA and allyl 2-hydroxypropionate, and the mass ratio of PVA, silica sol and allyl 2-hydroxypropionate added is 0.25:0.1:1;

[0054] Step 3, after the reaction is completed, the product is separated, washed with ethyl acetate, and dried at 60° C. to obtain a polyvinyl alcohol-silicon oxide-methacrylate copolymer;

[0055] Step 2: The reactor was kept in a mixed atmosphere of argon and oxygen, with the flow rates of argon and oxygen being 100 sccm, and then heated at room temperature and 10 -5The ITO conductive layer was deposited on the surface of a 20 μm flexible substrate layer (PET) at a pressure of 10 torr to a thickness of 80 nm; the reactor was then kept in an argon atmosphere of 1000 sccm and heated at room temperature and 10 -2 Depositing polyvinyl alcohol-silicon oxide-methacrylate copolymer on the surface of the ITO conductive layer under a pressure of 100 torr until the thickness of the polymer layer reaches 15 μm; during the above deposition process, when depositing in a plasma atmosphere, the RF power is maintained at 800 W;

[0056] Step 3: Then heat treat at 180° C. for 20 minutes to obtain the ITO film material for the flexible touch screen.

[0057] Embodiment 3:

[0058] Preparation of ITO film materials for touch screens:

[0059] Step 1: Preparation of polyvinyl alcohol-silicon oxide-methacrylate copolymer:

[0060] Step 1, adding a certain amount of deionized water, and adding appropriate amounts of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate to a reaction container, stirring evenly, adding PVA, heating to 80° C. and stirring until completely dissolved to obtain a mixture; wherein the addition amounts of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate are both 2% of the mass of PVA, and the mass ratio of PVA to deionized water is 5:80;

[0061] Step 2, in another container, hydroxypropyl methacrylate is mixed with silica sol (modulus 3.0), sodium dodecylbenzene sulfonate and ammonium persulfate to prepare a pre-emulsion, and the pre-emulsion is slowly added to the mixture obtained in step 1 under heating to 70°C and stirring conditions, and the dropping time is controlled to be 35 minutes. After the dropping is completed, the temperature is kept for 4 hours to carry out the polymerization reaction; wherein, the amount of sodium dodecylbenzene sulfonate in the pre-emulsion is 1% of the mass of hydroxypropyl methacrylate, the amount of ammonium persulfate added is 1% of the total mass of PVA and hydroxypropyl methacrylate, and the mass ratio of PVA, silica sol and hydroxypropyl methacrylate is 0.4:0.1:1;

[0062] Step 3, after the reaction is completed, the product is separated, washed with ethyl acetate, and dried at 60° C. to obtain a polyvinyl alcohol-silicon oxide-methacrylate copolymer;

[0063] Step 2: The reactor was kept in a mixed atmosphere of argon and oxygen, with the flow rate of argon being 100 sccm and the flow rate of oxygen being 1000 sccm, and then heated at room temperature and 10 -2 The ITO conductive layer was deposited on the surface of a 100 μm flexible substrate layer (PET) at a pressure of 10 torr to a thickness of 150 nm; the reactor was then kept in an argon atmosphere of 2000 sccm and heated at room temperature and 10-2 Depositing polyvinyl alcohol-silicon oxide-methacrylate copolymer on the surface of the ITO conductive layer under a pressure of 1000 W to a thickness of 5 μm; during the above deposition process, when depositing in a plasma atmosphere, the RF power is maintained at 1000 W;

[0064] Step 3: Then heat-treat at 160° C. for 60 min to obtain the ITO film material for the flexible touch screen.

[0065] Embodiment 4:

[0066] Preparation of ITO film materials for touch screens:

[0067] Step 1: Preparation of polyvinyl alcohol-silicon oxide-methacrylate copolymer:

[0068] Step 1, adding a certain amount of deionized water, and adding appropriate amounts of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate to a reaction container, stirring evenly, adding PVA, heating to 80° C. and stirring until completely dissolved, to obtain a mixture; wherein the addition amounts of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate are both 1.5% of the mass of PVA, and the mass ratio of PVA to deionized water is 0.1:30;

[0069] Step 2, in another container, hydroxyethyl methacrylate is mixed with silica sol (modulus 3.2), sodium dodecylbenzene sulfonate, and initiator ammonium persulfate to prepare a pre-emulsion, and the pre-emulsion is slowly added to the mixture obtained in step 1 under heating to 60°C and stirring conditions, and the dropping time is controlled to be 35 minutes. After the dropping is completed, the polymerization reaction is continued for 4 hours; wherein, the sodium dodecylbenzene sulfonate in the pre-emulsion is 1% of the mass of hydroxyethyl methacrylate, the amount of the initiator added is 0.3% of the total mass of PVA and hydroxyethyl methacrylate, and the mass ratio of PVA, silica sol and hydroxyethyl methacrylate added is 0.25:0.1:1;

[0070] Step 3, after the reaction is completed, the product is separated, washed with ethyl acetate, and dried at 60° C. to obtain a polyvinyl alcohol-silicon oxide-methacrylate copolymer;

[0071] Step 2: The reactor was kept in a mixed atmosphere of argon and oxygen, with an argon flow rate of 1000 sccm and an oxygen flow rate of 30 sccm, and then heated at room temperature and 10 -6 The ITO conductive layer was deposited on the surface of a 10 μm flexible substrate layer (PET) at a pressure of 10 torr to a thickness of 20 nm; the reactor was then kept in an argon atmosphere of 80 sccm and heated at room temperature and 10 -6Depositing polyvinyl alcohol-silicon oxide-methacrylate copolymer on the surface of the ITO conductive layer under a pressure of 1000 μm to a thickness of 20 μm; during the above deposition process, when depositing in a plasma atmosphere, the RF power is maintained at 500 W;

[0072] Step 3: Then heat treat at 170° C. for 40 minutes to obtain the ITO film material for the flexible touch screen.

[0073] Comparative Example 1:

[0074] Preparation of ITO film materials for touch screens:

[0075] Step 1: Preparation of polyvinyl alcohol-silicon oxide-methacrylate copolymer:

[0076] Step 1, add a certain amount of deionized water, and add appropriate amounts of OP-10 and sodium dodecyl sulfate in a reaction container, stir evenly, add PVA, heat to 80°C and stir until completely dissolved to obtain a mixture; wherein the added amounts of OP-10 and sodium dodecyl sulfate are both 1% of the mass of PVA, and the mass ratio of PVA to deionized water is 1:10;

[0077] Step 2, in another container, hydroxyethyl methacrylate, OP-10, and ammonium persulfate are mixed to prepare a pre-emulsion, and the pre-emulsion is slowly added to the mixture obtained in step 1 under heating to 70° C. and stirring conditions, and the dropping time is controlled to be 25 minutes. After the dropping is completed, the mixture is kept warm for 3 hours for polymerization reaction; wherein, the amount of OP-10 in the pre-emulsion is 1% of the mass of hydroxyethyl methacrylate, the amount of ammonium persulfate added is 0.5% of the total mass of PVA and hydroxyethyl methacrylate, and the mass ratio of PVA to hydroxyethyl methacrylate is 0.3:1;

[0078] Step 3, after the reaction is completed, the product is separated, washed with ethyl acetate, and dried at 60° C. to obtain a polyvinyl alcohol-silicon oxide-methacrylate copolymer;

[0079] Step 2: The reactor was kept in a mixed atmosphere of argon and oxygen, with the flow rates of argon and oxygen being 300 sccm each, and then heated at room temperature and 10 -3 The ITO conductive layer was deposited on the surface of a 30 μm flexible substrate layer (PET) at a pressure of 10 torr to a thickness of 50 nm; the reactor was then kept in an argon atmosphere of 300 sccm and heated at room temperature and 10 -4 Depositing polyvinyl alcohol-silicon oxide-methacrylate copolymer on the surface of the ITO conductive layer under a pressure of 100 μm until the thickness of the polymer layer reaches 10 μm; during the above deposition process, when depositing in a plasma atmosphere, the RF power is maintained at 800 W;

[0080] Step 3: Then heat treat at 160° C. for 50 min to obtain the ITO film material for the flexible touch screen.

[0081] Comparative Example 2:

[0082] Preparation of ITO film materials for touch screens:

[0083] Step 1: Preparation of polyvinyl alcohol-silicon oxide-methacrylate copolymer:

[0084] Step 1, add a certain amount of deionized water, and add appropriate amounts of OP-10 and sodium dodecyl sulfate in a reaction container, stir evenly, add PVA, heat to 80°C and stir until completely dissolved to obtain a mixture; wherein the added amounts of OP-10 and sodium dodecyl sulfate are both 1% of the mass of PVA, and the mass ratio of PVA to deionized water is 1:10;

[0085] Step 2, in another container, hydroxyethyl methacrylate is mixed with silica sol (modulus 3.2), OP-10 and ammonium persulfate to prepare a pre-emulsion, and the pre-emulsion is slowly added to the mixture obtained in step 1 under heating to 70°C and stirring conditions, and the dropping time is controlled to be 25 minutes. After the dropping is completed, the temperature is kept for 3 hours to carry out the polymerization reaction; wherein, the OP-10 in the pre-emulsion is 1% of the mass of hydroxyethyl methacrylate, the amount of ammonium persulfate added is 0.5% of the total mass of PVA and hydroxyethyl methacrylate, and the mass ratio of PVA, silica sol and hydroxyethyl methacrylate is 0.3:0.15:1;

[0086] Step 3, after the reaction is completed, the product is separated, washed with ethyl acetate, and dried at 60° C. to obtain a polyvinyl alcohol-silicon oxide-methacrylate copolymer;

[0087] Step 2: The reactor was kept in a mixed atmosphere of argon and oxygen, with the flow rates of argon and oxygen being 300 sccm each, and then heated at room temperature and 10 -3 The ITO conductive layer was deposited on the surface of a 30 μm flexible substrate layer (PET) at a pressure of 10 torr to a thickness of 50 nm; the reactor was then kept in an argon atmosphere of 300 sccm and heated at room temperature and 10 -4 Depositing polyvinyl alcohol-silicon oxide-methacrylate copolymer on the surface of the ITO conductive layer under a pressure of 100 μm until the thickness of the polymer layer reaches 10 μm; during the above deposition process, when depositing in a plasma atmosphere, the RF power is maintained at 800 W;

[0088] Step 3: Then heat treat at 160° C. for 50 min to obtain the ITO film material for the flexible touch screen.

[0089] Comparative Example 3:

[0090] Preparation of ITO film materials for touch screens:

[0091] Step 1: Preparation of polyvinyl alcohol-silicon oxide-methacrylate copolymer:

[0092] Step 1, add a certain amount of deionized water, and add appropriate amounts of OP-10 and sodium dodecyl sulfate in a reaction container, stir evenly, add PVA, heat to 80°C and stir until completely dissolved to obtain a mixture; wherein the added amounts of OP-10 and sodium dodecyl sulfate are both 1% of the mass of PVA, and the mass ratio of PVA to deionized water is 1:10;

[0093] Step 2, in another container, methyl methacrylate, silica sol (modulus 3.2), OP-10, and ammonium persulfate are mixed to prepare a pre-emulsion, and the pre-emulsion is slowly added to the mixture obtained in step 1 under heating to 70°C and stirring conditions, and the dropping time is controlled to be 25 minutes. After the dropping is completed, the temperature is kept for 3 hours to carry out the polymerization reaction; wherein, the OP-10 in the pre-emulsion is 1% of the mass of methyl methacrylate, the amount of ammonium persulfate added is 0.5% of the total mass of PVA and methyl methacrylate, and the mass ratio of PVA, silica sol and methyl methacrylate added is 0.3:0.1:1;

[0094] Step 3, after the reaction is completed, the product is separated, washed with ethyl acetate, and dried at 60° C. to obtain a polyvinyl alcohol-silicon oxide-methacrylate copolymer;

[0095] Step 2: The reactor was kept in a mixed atmosphere of argon and oxygen, with the flow rates of argon and oxygen being 300 sccm each, and then heated at room temperature and 10 -3 The ITO conductive layer was deposited on the surface of a 30 μm flexible substrate layer (PET) at a pressure of 10 torr to a thickness of 50 nm; the reactor was then kept in an argon atmosphere of 300 sccm and heated at room temperature and 10 -4 Depositing polyvinyl alcohol-silicon oxide-methacrylate copolymer on the surface of the ITO conductive layer under a pressure of 100 μm until the thickness of the polymer layer reaches 10 μm; during the above deposition process, when depositing in a plasma atmosphere, the RF power is maintained at 800 W;

[0096] Step 3: Then heat treat at 160° C. for 50 min to obtain the ITO film material for the flexible touch screen.

[0097] Performance Testing

[0098] The materials prepared in the examples and comparative examples were subjected to bending tests, and the test method was as follows:

[0099] Set the size to 10 The above materials with a length of 2 cm were subjected to 1000 inward bending tests under the condition of a wire rod diameter of 5 mm, with a bending angle of 0-180°. During the bending process, a multimeter was used to measure the resistance value after each bending, and it was observed whether separation and peeling occurred between the layers after 1000 bendings, as shown in Table 1:

[0100] Table 1:

[0101]

[0102] The ITO film material prepared in the example was immersed in a 5 mol / L hydrochloric acid solution for 48 h. There was no corrosion mark on the surface of the ITO film material, and no water seepage and blistering phenomenon, indicating that the prepared ITO film material has strong chemical stability and high interface strength.

[0103] The test results in Table 1 show that the ITO film material prepared by the method of the present invention has good conductivity, flexibility and mechanical strength, and also has excellent light transmittance; when no silica sol is added (Comparative Example 1), polyvinyl alcohol and hydroxyl-containing acrylic monomers only undergo polymerization reaction, and crosslinking is reduced, or when excessive silica sol is added (Comparative Example 2), the crosslinking between the silica sol and polyvinyl alcohol and hydroxyl-containing acrylic monomers is too strong and leads to excessive introduction of silicon oxide, or when the acrylate monomer does not contain hydroxyl groups (Comparative Example 3), the added silica sol cannot react with the acrylic monomer, the crosslinking is reduced, and the bonding of silicon oxide in the polymer becomes weak, all of which affect the performance of the prepared ITO film material.

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An ITO film material for a flexible touch screen, characterized in that: It comprises a flexible substrate layer, an ITO conductive layer and a polymer layer, wherein the ITO conductive layer is arranged on one surface of the flexible substrate layer, the polymer layer is arranged on a side surface of the ITO conductive layer away from the flexible substrate layer, and the components of the polymer layer include polyvinyl alcohol-silicon oxide-methacrylate copolymer; The preparation method of the polyvinyl alcohol-silicon oxide-methacrylate copolymer comprises: Step 1, add an appropriate amount of emulsifier and dispersant to deionized water, stir evenly, add PVA, heat until dissolved, and obtain a mixture; Step 2, mixing the acrylic acid ester monomer with silica sol, emulsifier and initiator to prepare a pre-emulsion, and slowly dropping it into the mixture obtained in step 1 under heating and stirring conditions. After the dropping is completed, continue to keep the temperature to carry out the polymerization reaction; Step 3: After the reaction is completed, the obtained product is separated, washed and dried to obtain a polyvinyl alcohol-silicon oxide-methacrylate copolymer; The added mass ratio of the PVA, silica sol and acrylate monomer is 0.25-0.4:0.1:1; the modulus of the silica sol is 2.8-3.2; and the acrylate monomer is selected from acrylate monomers with hydroxyl groups.

2. The ITO film material for a flexible touch screen according to claim 1, characterized in that: The hydroxyl-containing acrylic ester monomer is at least one of hydroxyethyl methacrylate, allyl 2-hydroxypropionate and hydroxypropyl methacrylate.

3. The ITO film material for a flexible touch screen according to claim 1, characterized in that: In step 2, the pre-emulsion is added dropwise for 20 to 35 minutes.

4. The ITO film material for a flexible touch screen according to claim 1, characterized in that: In step 2, the polymerization reaction temperature is 60-80° C., and the reaction time is 2-4 hours.

5. The ITO film material for a flexible touch screen according to claim 1, characterized in that: In step 2, the initiator includes at least one of ammonium persulfate and potassium persulfate.

6. The ITO film material for a flexible touch screen according to claim 1, characterized in that: The thickness of the flexible substrate layer is 10-100 μm, the thickness of the ITO conductive layer is 10-150 nm, and the thickness of the polymer layer is less than 30 μm.

7. The ITO film material for a flexible touch screen according to claim 1, characterized in that: The flexible substrate layer includes at least one of PET, PC, PI, PES and PE.

8. A method for preparing an ITO film material for a flexible touch screen according to any one of claims 1 to 7, characterized in that: include: Step 1: depositing an ITO conductive layer on the flexible substrate layer, and then depositing a polyvinyl alcohol-silicon oxide-methacrylate copolymer on the ITO conductive layer to prepare a polymer layer; Step 2: Finally, heat treatment is performed at 160-180° C. for 20-60 min to obtain the ITO film material for the flexible touch screen.

Citation Information

Patent Citations

  • Transparent electrode structure for touchscreen using electron beam evaporation and touchscreen panel comprising same

    KR101385951B1

  • Silica sol / polyacrylic ester emulsion with high silicon content and preparation method of silica sol / polyacrylic ester emulsion

    CN104530302A

  • Flexible transparent conductive membrane, preparation method thereof and flexible touch screen

    CN107705882A